Abdominal pain mimicking dysmenorrhea in luteal phase. Issue 3 (September 2018) - Nishida, Masato; Itagaki, Hiroya; Otsubo, Yasuo; Ichikawa, Ryota; Arai, Yuko; Sakanaka, Miyako
We treated four patients with severe abdominal pain in the luteal phase that showed a remarkable resemblance to dysmenorrhea. The symptoms began when the patients were in their twenties and thirties, and the pain was identical to the high phase of basal body temperature. No other abnormal findings were revealed in physical examinations, except for leiomyoma in two patients. Oral contraceptive use led to symptom exacerbation, while gonadotropin-releasing hormone agonist administration completely inhibited the pain. One patient underwent a hysterectomy for leiomyoma, with ovulation later confirmed, though luteal phase abdominal pain completely disappeared. Based on our findings, the postulated mechanism for the pain is uterine contractions induced by progesterone through various mechanisms. The symptoms in our patients were successfully treated by ovulation inhibition obtained with cyclic administration of conjugated estrogen.